CD207⁺ cells recruitment to the vaccination site and draining lymph nodes after the administration of DC-Apo/Nec vaccine in mice - Ruiz, María Sol (2014)
De novo ectopic lymphoid tissue formation is known to occur in certain disease and inflammatory settings. After an effective vaccination with dendritic cells (DC) charged with melanoma apoptotic/necrotic cells (Apo/Nec), a subcutaneous tertiary lymphoid structure was organized, where retained vaccine cells interacted with recruited inflammatory and T cells. In this work we report for the first time the recruitment of two morphologically different CD207(+) cells to vaccination site. The time-course behavior of CD207(+) cells was reciprocal between vaccination site and draining lymph nodes (DLNs). After 6-10 days, CD207(+) cells localized at the paracortical region of DLNs, in close contact with T cell population. DLNs were enriched in a peculiar MHCII(+) CD11c((-)) CD207(+) population, whose role remains to be determined. Whether CD207(+) cells migration to the vaccination site can be associated with a differential anti-tumoral response remains as an open and exciting question.